Sensory Characteristics Of Tamarillo (Solanum betaceum) Jam With Pectin Addition As Gelling Agent - Rahma Izah, Nurul; Holinesi, Rahmi; Faridah, Anni; Mustika, Sari (Jurnal Pendidikan Tata Boga dan Teknologi, 2024)
The objective of this study is to examine the impact of adding pectin at levels of 0% (X0), 0.5% (X1), 1% (X2), and 1.5% (X3) on the color, taste, texture (soft and spreadable), and aroma of the tamarillo jam that is made. This kind of study uses a fully randomized design approach (RAL) with four treatments and three replications. It is a pure experiment. Three small panelists participated in organoleptic tests as part of this study to assess the pectin-added tamarindo jam's quality based on the method of preparation. Variant analysis (ANAVA) was used to statistically examine the collected data. The Duncan test should be performed if Fcal exceeds Ftable. The finest quality jam was produced by adding 0.5% (X1) pectin, as evidenced by the jam's crimson color (3.89), less fragrant tamarillo aroma (2.66), soft and spreadable texture (4.00), and sweet acidity taste (3.78).